Millions Fed: Proven successes in agricultural development - Pandya-Lorch, Rajul; Spielman, David J.; Pingali, Prabhu; Montemayor, Raul; von Braun, Joachim (2009)
Rajul Pandya-Lorch (IFPRI); David J. Spielman, IFPRI; Prabhu Pingali, The Bill & Melinda Gates Foundation; Raul Montemayor, Federation of Free Farmers Cooperatives Inc.; Chair: Joachim von Braun, (IFPRI) 12th November 2009, International Food Policy Research Institute (IFPRI), Washington D.C.